2017
DOI: 10.1177/0956797617696311
|View full text |Cite
|
Sign up to set email alerts
|

Does Knowing Hurt? Perceiving Oneself as Overweight Predicts Future Physical Health and Well-Being

Abstract: Self-identification as being 'overweight' may be associated with adverse health outcomes, yet prospective evidence examining this possibility is lacking. Over 7-years, we examined associations between perceived overweight and subsequent health in a sample of 3,582 US adults. Perceived overweight predicted longitudinal declines in subjective health (d =.22, p <.001), increases in depressive symptoms (d =.09, p < .05), and raised levels of physiological dysregulation (d =.24, p <.001) as gauged by clinical indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
(81 reference statements)
4
31
0
1
Order By: Relevance
“…Overall, there was strong evidence to suggest that individuals who perceived themselves as overweight were more likely to gain weight over time than those who perceived themselves as normal weight across most participant subgroups. Results of a supplementary analysis of a subset of nine studies that assessed weight change using objectively measured BMI only (i.e. those that met quality criterion 8; Table S4a) were consistent with the main evidence synthesis: there was strong evidence to indicate that overall, perceived overweight was associated with weight gain over time.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Overall, there was strong evidence to suggest that individuals who perceived themselves as overweight were more likely to gain weight over time than those who perceived themselves as normal weight across most participant subgroups. Results of a supplementary analysis of a subset of nine studies that assessed weight change using objectively measured BMI only (i.e. those that met quality criterion 8; Table S4a) were consistent with the main evidence synthesis: there was strong evidence to indicate that overall, perceived overweight was associated with weight gain over time.…”
Section: Resultssupporting
confidence: 62%
“…Initial database searches identified 10,398 unique records, and an additional 41 articles were identified by authors, from the reference lists of eligible articles or from supplementary searches. Full‐text review of 366 articles was completed, and 74 articles (indicated with asterisks in reference list) that described 78 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, parents who perceive their child as overweight might pressure the child to lose weight or at least watch what they are eating; such pressure is stressful for the child (16). Second, previous research has shown that parent perception of child overweight is associated longitudinally with the child’s self-perception of weight (4), and this weight self-perception is associated with subsequent physiological dysregulation (10). Parent perception may thus contribute to child CRP by shaping the child’s self-perceptions of their weight over time.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein (CRP), in particular, is a common inflammatory marker implicated in stress (7) as well as greater adiposity (8). In adulthood, the stress and stigma of overweight is associated with greater inflammation, independent of the individual’s adiposity (9, 10). Parental perception of the child’s weight may likewise be stressful and thus apparent in the child’s level of inflammation.…”
mentioning
confidence: 99%